Waterpower in Lowell : engineering and industry in nineteenth-century America - Malone, Patrick M. (Johns Hopkins Introductory Studies in the History of Technology, 2009)
Its clear and instructional discussions of hydraulic technology and engineering principles make it a useful resource for a range of courses, including the history of technology, urban history, and American business history.